(3eOi JhGab CgOGa heVGejf cJH GddZI GdYQHjI GdqQSeqjI GdqKfjI eY GdGgOGa GdeMqOOI aj GdefgL GdqQSejs - (3eWQ, aGWeI eMeOs ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3cdjI GdJQHjI, GdYeGOIs, 2015)
(3gOaJ GdOQGSI Edi JMOjO eOi GdJhGab Hjf CgOGa heVGejf cJH GddZI GdYQHjI GdQSejI (B((3bQGAI hbhGYO(B) (3aj GdMdbI GdKGfjI ef GdJYdje GdCSGSj hGdCgOGa GdeMOOI aj GdefgL GdQSej, HGdEVGaI Edi JUfja CgOGa GdcJH Vef GdeLGdGJ GdKdGKI(B: (3GdYbdj (B((3GdeYQaj(B)(3, hGdYGWaj (B((3GdhLOGfj(B)(3, hGdMQcj (B((3GdfaS(B- (3MQcj(B). (3EJHYJ GdOQGSI GdefgL GdhUaj GdJMdjdj MjK GSJNOeJ CSdhH JMdjd GdeMJhi, hbO JchfJ YjfI GdHMK ef eLehY GdCgOGa GdNGUI (B(1273 (3gOakG(B) (3GdYGFOI dOQhS eMGhQ GdcJH aj GdUaha GdKdGKI (B((3GdQGHY, GdNGeS, hGdSGOS(B)(3, ceG JchfJ CjVG ef GdCgOGa GdYGeI ddefGgL, hGdCgOGa GdYGeI ddZI GdYQHjI, hGdCgOGa GdNGUI dgPg GdeGOI aj GdMdbI GdKGfjI GdeJVefI aj GdeQShe (B10227. (3hJe JUeje HWGbI dJMdjd GdCgOGa HfGA Ydi JUfjaGJ(B: (3OHdhe, cQGKhhd, hSeHShf, hLQi GdJCcO ef UObgG hKHGJgG(B. (3HjfJ GdfJGFL JhGabkG bhjkG Hjf CgOGa GdcJH hCgOGa GdefgL GdQSej, hJQGhM GdJhGab ef LgI CgOGa GdcJH eG Hjf bhqj (B((3eY GdCgOGa GdYGeI ddefGgL(B) (3hLjO (B( (3eY GdCgOGa GdYGeI ddZI hCgOGagG GdNGUI aj GdMdbI GdKGfjI(B). (3hde jSLd Cj JhGab Hjf CgOGa GdcJH hGdgOa GdYGe ddefGgL, GdPj jYfi HGcJSGH dZI CLfHjI hGdgOa GdYGe ddeGOI GdPj jNJU HGcJSGH egGQI GdJYHjQ ef NdGd JYQjH GdfUhU(B. (3ceG cTa JMdjd GdCgOGa gjefI GdeLGd GdYbdj Ydi eLed GdCgOGa aj GdUaha GdKdGKI (B(72.98%)(3, aj Mjf MGR GdeLGd GdYGWaj Ydi fSHI HSjWI (B(23.88%)(3, jdjg GdeLGd GdMQcj HfSHI VFjdI (B(3.14%).s
(3GdfhY (B: (3QSGdIs
Keywords: Public Sector Secondary Education Arabic Language education Textbooks; Secteur Public Cycle Secondaire L$1 (Benseignement de la langue Arabe Livres Scolairess; (3GdJYdje GdQSej GdeQMdI GdKGfhjI JYdje GddZI GdYQHjI GdcJGH GdeOQSjs